Studi Sosiolinguistik pada Nadhoman Terjemah Kitab Syu’abul Iman Karya KH. A Wahab Muhsin - Basajan, abdul rahman (Jaladri : Jurnal Ilmiah Program Studi Bahasa Sunda, 2024)
Sociolinguistic studies are part of modern linguistic studies which cover all linguistic phenomena and their communities. This study can explain word preferences or language structures that differentiate one literary work from another based on the relationship between individuals, populations, periodization and people's lifestyle patterns. The source of sociolingistics research is all types of communication that use language, both spoken and written in all varieties of languages ​​in the world. This research aims to describe sociolinguistic relationships and traces of their application in Nadhoman's "Translation of Syu'abul Iman". The data used in this research are all aspects of perspective studies which include figurative sentences in the form of symbols, images, figurative language or figures of speech, as well as diction or choice of words as well as expressions in the form of loanwords, theme idioms, diction, language style, imagination and messages that describe the influence sociological and linguistic aspects of the translation of the book Syu'abul Iman by KH.A Wahab Muhsin in the form of a translation of the book Syu'abul Iman which was compiled in 1967. Researchers indicate that there are linguistic values ​​related to the situation and social relations in it. To prove this, the author analyzes it using descriptive qualitative methods. The data collection technique in this research is a reading-note technique. The technique is carried out by reading, taking notes for analysis based on the perspective study. The research results obtained prove that sociolinguistics is very influential on the building blocks of the translation of the book Syu'abul Iman.Keywords: Sociolinguistics, Sundanese Nazhoman, Translation.